Inovasi dan integritas ilmu: Heuristik lanjutan dan pancasila sebagai pilar pengembangan pengetahuan - Buchori, Azzahra Nadiefa Qolby (Maliki Interdisciplinary Journal, 2025)
This journal discusses the importance of advanced heuristics in the development of scientific knowledge, particularly in addressing complex and uncertain situations. Heuristics promote flexible and open-minded thinking, enabling science to grow adaptively. On the other hand, the development of science in Indonesia must also take into account local values and national ethical foundations. In this context, Pancasila serves as a moral and philosophical foundation that guides science to remain relevant, humane, and oriented toward social justice. The integration of advanced heuristics and Pancasila produces a scientific approach that is not only technically advanced but also socially and culturally meaningful.